Achieving tumour control when suspecting sinus fat involvement during robot‐assisted partial nephrectomy: step‐by‐step. (23rd October 2018) - Bertolo, Riccardo; Garisto, Juan; Sagalovich, Daniel; Dagenais, Julien; Agudelo, Jose; Kaouk, Jihad
Abstract : Objectives: To report a single expert robotic surgeon's step‐by‐step surgical technique for achieving local cancer control during robot‐assisted PN (RAPN) for T3 tumours. Patients and methods: Since January 2010 to December 2016, the institutional RAPN database was queried for patients who underwent transperitoneal RAPN performed by a single surgeon for tumours ≤4 mm from the collecting system at preoperative computed tomography (three points on the ' N [Nearness]' R.E.N.A.L. nephrometry‐score item) that were pT3a involving sinus fat at final pathology. Baseline characteristics, perioperative and oncological outcomes (particularly positive surgical margins, PSMs), were identified. Results: Of 1497 masses that underwent RAPN, 512 scored 3 points on the ' N ' item of the R.E.N.A.L. nephrometry score assessment. In all, 24 patients had pT3a tumours involving sinus fat at final pathology and represented the analysed cohort. RAPN were performed according to the here described technique. No PSMs were reported. Trifecta achievement was 54.2%. Within a median follow‐up of 30 months, two and one patients had recurrence or metastasis, respectively. Two patients died unrelated to renal cancer. Retrospective analysis and limited follow‐up represent study limitations. Conclusion: In a selected cohort of patients with renal tumours near the sinus fat at baseline R.E.N.A.L. nephrometry score assessment and confirmed pT3a at final pathology, the described RAPN technique was able to achieve optimal local cancer control.